A violação dos direitos humanos frente Ã crise político-jurídica na Líbia - Annoni, Danielle; Freitas, Márcia Marcondes Diniz de (Meridiano 47 - Journal of Global Studies, 2017)
This article presents elements for the discernment of the crisis in the Middle East and North of Africa, particularly the specific case of Libya, which differs from the others because of the strength of Muammar Kadaffi. Also discusses the expectation democratic effectiveness and impact on human rights.